2012
DOI: 10.1021/ja3073929
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silylene-Bridged Endohedral Metallofullerene Lu3N@Ih-C80

Abstract: Functionalization of endohedral metallofullerenes has been shown to differ depending on photochemical or thermal pathways. We report that Lu(3)N@I(h)-C(80) reacts with thermally generated bis(2,6-diethylphenyl)silylene with high selectivity and forms monosilylated derivative 1b. Unexpectedly, 1b undergoes photochemical conversion to afford isomer 1a under ambient light. These adducts were characterized using NMR, visible-near-IR spectroscopy, and matrix-assisted laser desorption ionization time-of-flight mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…[12] Cyclopropanation-type reactions have been used to modify EMFs to yield methanofullerenes [13] and recently, azafulleroids [14] and silylene-bridged derivatives. [15] There are two distinct addition sites available on the I h isomer of C 80 fullerenes: C À C bonds at [6,6] ring junctions (pyrene-type sites) and CÀC bonds at [5,6] ring junctions (corannulenetype sites). In 2005, Poblet and co-workers [16] reported that the corannulene [5,6] bonds closest to the Sc atoms have the highest strain of all bonds in the I h -C 80 cage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Cyclopropanation-type reactions have been used to modify EMFs to yield methanofullerenes [13] and recently, azafulleroids [14] and silylene-bridged derivatives. [15] There are two distinct addition sites available on the I h isomer of C 80 fullerenes: C À C bonds at [6,6] ring junctions (pyrene-type sites) and CÀC bonds at [5,6] ring junctions (corannulenetype sites). In 2005, Poblet and co-workers [16] reported that the corannulene [5,6] bonds closest to the Sc atoms have the highest strain of all bonds in the I h -C 80 cage.…”
mentioning
confidence: 99%
“…[13, 19,20] Although nitrogen [14] and silicon bridges [15] at [5,6] bonds have been reported, the corresponding methano adducts have remained elusive.…”
mentioning
confidence: 99%
“…In fact, thermal reaction of Lu 3 N@I h (7)-C 80 with the precursor yielded two isomers of the silylene adducts, of which a major isomer was isolated and the structure solved by single-crystal XRD (Figure 19). 131 The other was rather unstable. It was transformed slowly into the major isomer under ambient light.…”
Section: Sbclmentioning
confidence: 98%
“…Chemical functionalization of fullerenes has been attracting much attention from both mechanistic and synthetic viewpoints . An introduction of heteroatoms such as electropositive silicon has been known as an effective method to modify the electronic characteristics of empty fullerenes and endohedral metallofullerenes . The facile silylation reactions of fullerenes have been described using reactive silicon compounds such as silylenes , disiliranes , and silyl radicals .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative procedures for silylation of fullerenes are desirable for the development of various silylated fullerene‐based materials. Recently, thermal addition reactions of endohedral metallofullerenes with disiliranes, digermiranes , siliranes , and silylenes have been demonstrated to afford the corresponding silylated derivatives. In addition, thermal reactions of C 60 with siliranes have been reported to afford carbosilylated and monosilylated products .…”
Section: Introductionmentioning
confidence: 99%